Fast kinetics of monoclinic VO2(B) bulk upon magnesiation via DFT+U calculations. Issue 4 (7th January 2022) - Gao, Danmei; Dong, Jingren; Xiao, Renchao; Shang, Bo; Yu, Danmei; Chen, Changguo; Liu, Yuping; Zheng, Kai; Pan, Fusheng
Abstract : The Mg 2+ diffusivity of 1.62 × 10 −7 cm 2 s −1 is comparable to that of Li + at 300 K, demonstrating the high mobility and fast kinetics of VO2 (B) as a potential host material. Abstract : Although magnesium rechargeable batteries (MRBs) have gained considerable attention, research relating to MRBs is still in its infancy. One issue is that magnesium ions are difficult to reversibly (de)intercalate in most electrode materials. Among various available cathodes, VO2 (B) is a promising layered cathode material for use in MRBs. Totally different from monolayer VO2, the magnesiation mechanism in monoclinic bulk VO2 (B) has not been clearly clarified to this day. For the first time, we systematically investigated the influence of magnetism and van der Waals (vdW) forces on the electronic structure and diffusion kinetics of magnesium in bulk VO2 (B) using a series of DFT+U calculations. The Mg diffusivity can reach a high value of 1.62 × 10 −7 cm 2 s −1 at 300 K, which is comparable to Li + . These results demonstrate that VO2 (B) is a potential host material with high mobility and fast kinetics.